Analysis of prevalence of PTSD and its influencing factors among college students after the Wenchuan earthquake - Fu Yan; Chen Yongshun; Wang Jin; Tang Xiaohui; He Jieyun; Jiao Miaorui; Yu Chunhua; You Guiying; Li Junying (BMC, 2013)
Abstract Background This study explored the prevalence and severity of post-traumatic stress disorder (PTSD) in college students who lived in earthquake center one year after the Wenchuan earthquake on May 12, 2008, the factors affecting the prevalence of PTSD was also investigated. Methods 2987 students studying at the senior normal school in Tibetan autonomous region which was one of the most devastated regions were selected for this study. The PTSD Checklist-Civilian Version (PCL-C) was used as a screening instrument. Results A total of 420 cases (14.1%) were diagnosed with PTSD, among which mild, moderate, severe and extreme symptoms were reported in 122, 185, 106 and 7 cases, respectively. The PTSD prevalence in college students lived in the severely affected area was significantly higher than that in the less severe area (P < 0.001). According to the multivariate logistic regression analysis, the students who were injured in the earthquake, those lost their first degree relative, and those confronted with dead bodies were more likely to express PTSD. Male students were more prone than female students to develop PTSD. However, the students who received psychological tutorship were less prone to express PTSD. Conclusions At one year after the earthquake, the PTSD rate in college students in the severely affected area was high. The social support, psychological help and rehabilitation project should be strengthened to improve their ability to cope with the trauma.